Coconut oil for utility transformers – Environmental safety and sustainability perspectives. (August 2022) - Das, Anu Kumar; Ch Shill, Dayal; Chatterjee, Saibal
Abstract: Nowadays, the electric utility is witnessing a paradigm shift from conventional mineral-based transformer oils that are exhausting, ecologically unsafe, and verified hazardous to natural esters that are renewable, environmentally friendly, and safe. Day-by-day, the pressures to decrease liability risks of utility transformers filled with mineral oils are rising whereas there are challenges to increase network efficiency and implement more "eco-friendly" alternatives in the electric utility. In the past 30 years, there has been a reappearance of natural ester-based transformer oils due to their biodegradability and fire safety credentials. Meanwhile, new vegetable oils rarely used so far in utility transformers are also being researched for their dielectric performance. Coconut oil is one such new vegetable oil recently studied and found to have good dielectric and physicochemical properties for use in the transformer. This paper examines and relates vegetable oils, particularly coconut oil, with mineral oil in terms of eco-toxicity properties and biodegradability. It also discusses the sustainability aspects and market potential of coconut oil, and concisely presents the eco-mark schemes to promote environmental conservation. In short, this paper provides electric utility, transformer manufacturers, and users about the environmental safety and prospect of transformer oil based on oil extracted from "coconut". Highlights: Eco-toxicity and biodegradability of vegetable oil, esp. coconut oil, are compared with mineral oil used for transformers. Coconut oil is fully biodegradable and a sustainable resource with low environmental impact. From worker health and fire safety aspects, coconut oil is safe and considered to be non-toxic. Need to encourage value addition and product diversification in coconut oil for non-traditional purposes like transformers.